BREASTFEEDING AND ITS EFFECT ON WEIGHT GAIN, NUTRITIONAL STATUS, AND ILLNESS INCIDENCE AMONG INFANTS AGED 1 – 5 MONTHS - Priyasna, Irpan; Dewanti, Lintang Purwara; Wahyuni, Yulia (JHE (Journal of Health Education), 2019)
Background: The prevalence of exclusive breastfeeding among infants aged 0-6 months in 2014 was 52.3%, then the prevalence of exclusive breastfeeding among infants aged 0-6 months in DKI Jakarta in 2014 was 67.1%. The low level of exclusive breastfeeding has an effect on the inadequate nutrition intake for infants that can cause growth and development disorder. This study was conducted to determine the association between breastfeeding with weight gain, nutritional status and illness incidence among infants aged 1-5 months in Grogol, West Jakarta. Methods: It was cross sectional study design, the population in this study were 96 infants aged 1-5 months recorded in all Posyandu in the area of ??Grogol, West Jakarta. The sample in this study were 47 infants selected by purposive sampling. Data were analyzed with chi-square and fisher exact tests. Results: The results showed that there were no association between breastfeeding with weight gain (p = 0.989), nutrition status based on weight/age (p=1.000), length/age (p=0.237), and weight/length (p=0.352). There was association between breastfeeding with illness incidence (p<0.01). Conclusion: There is significant association between breastfeeding with illness incidence among infant aged 1 ? 5 months.